2023
DOI: 10.1002/hon.3143
|View full text |Cite
|
Sign up to set email alerts
|

Novel agents in relapsed/refractory diffuse large B‐cell lymphoma

Abstract: Patients with relapsed or refractory (R/R) diffuse large B‐cell lymphoma (DLBCL), ineligible for or relapsing after autologous stem‐cell transplant or chimeric antigen‐receptor T‐cell therapies have poor outcomes. Several novel agents, polatuzumab vedotin, tafasitamab, loncastuximab tesirine, and selinexor, have been approved and offer new opportunities for this difficult to treat population. Studies are evaluating combination of these agents with chemotherapy and other emerging therapies. Additionally, advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 104 publications
(142 reference statements)
0
2
0
Order By: Relevance
“…After the introduction of rituximab, which showed improved results for DLBCL, a ceiling effect of first‐line rituximab‐based immunochemotherapy has been observed over the last decade, 6–29 until the emergence of polatuzumab vedotin. Currently, two antibody drug conjugates (polatuzumab vedotin and loncastuximab tesirine) have been approved for previously untreated or relapsed/refractory DLBCL 44–46 . The pilot study from the POLARIX trial demonstrated 2‐year EFS and PFS benefits of pola‐R‐CHP compared with R‐CHOP in patients with intermediate‐ and high‐risk DLBCL 32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the introduction of rituximab, which showed improved results for DLBCL, a ceiling effect of first‐line rituximab‐based immunochemotherapy has been observed over the last decade, 6–29 until the emergence of polatuzumab vedotin. Currently, two antibody drug conjugates (polatuzumab vedotin and loncastuximab tesirine) have been approved for previously untreated or relapsed/refractory DLBCL 44–46 . The pilot study from the POLARIX trial demonstrated 2‐year EFS and PFS benefits of pola‐R‐CHP compared with R‐CHOP in patients with intermediate‐ and high‐risk DLBCL 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, two antibody drug conjugates (polatuzumab vedotin and loncastuximab tesirine) have been approved for previously untreated or relapsed/refractory DLBCL. 44 , 45 , 46 The pilot study from the POLARIX trial demonstrated 2‐year EFS and PFS benefits of pola‐R‐CHP compared with R‐CHOP in patients with intermediate‐ and high‐risk DLBCL. 32 The potent therapeutic efficacy of pola‐R‐CHP might be attributed to the characteristics of the highly specific targeting ability and potent killing effect of polatuzumab vedotin.…”
Section: Discussionmentioning
confidence: 99%